Pandoraea sp. RB-44, A Novel Quorum Sensing Soil Bacterium - Robson Ee Han-Jen; Yin Wai-Fong; Chan Kok-Gan (Sensors, 2013)
Proteobacteria are known to communicate via signaling molecules and this process is known as quorum sensing. The most commonly studied quorum sensing molecules are N-acylhomoserine lactones (AHLs) that consists of a homoserine lactone moiety and an N-acyl side chain with various chain lengths and degrees of saturation at the C-3 position. We have isolated a bacterium, RB-44, from a site which was formally a landfill dumping ground. Using matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) mass spectrometry analysis, this isolate was identified as a Pandoraea sp.which was then screened for AHL production using biosensors which indicated its quorum sensing properties. To identify the AHL profile of Pandoraea sp. RB-44, we used high resolution tandem mass spectrometry confirming that this isolate produced N-octanoylhomoserine lactone (C8-HSL). To the best of our knowledge, this is the first report that showed quorum sensing activity exhibited by Pandoraea sp. Our data add Pandoraea sp. to the growing number of bacteria that possess QS systems.